The last checkmate : a novel - Saab, Gabriella (William Morrow, an imprint of HarperCollinsPublishers, 2021)
Vowing to avenge the murder of her family, Maria, a young Polish resistance worker imprisoned in Auschwitz, plays chess in exchange for her life, and, in doing so, challenges the man who destroyed her family to one last game that will end in either failure or justice.